STUDENT ENGAGEMENT AND MOTIVATION IN A VOCATIONAL ENGLISH PROJECT BASED LEARNING - Arik Susanti; Anis Trisusana (Universitas Ahmad Dahlan)
This study aimed to describe the student engagement and motivation in studying English through Project Based Learning (PjBL). PjBL provides students the freedom to be critical thinkers and problem solvers. Moreover, it places the students in situations that require authentic use of language in order to communicate and to present. The method used was qualitative since the objective of the research was to describe the development of the students’ creativity. The participants were 40 students and 2 English teachers in Vocational High Schools in East Java Province. The data were gained through interview and classroom observation. The data from interview were transcribed and analyzed qualitatively, and the data from classroom observation were coded and analyzed qualitatively. The results showed that PjBL could increase the students’ motivation. The students were interested in completing their projects and enthusiastic in learning English. Therefore, PjBL is recommended to be used in English learning to encourage the student engagement and motivation.